Intrusion Detection by Port Scan Using Snort - Alkhushayni, Suboh Mohammad Shehadah (2008)
Network intrusion detection systems (NIDS) are an important part of any network security architecture. They provide a layer of defense which monitors network traffic for predefined suspicious activity or patterns, and alert system administrators when potential hostile traffic is detected. Network Intrusion Detection Systems (NIDS) perform deep packet inspection on packet payloads to identify, prevent, and inhibit malicious attacks over the Internet[l]. Snort is a lightweight intrusion detection system that can log packets coming across your network. This program can be used on smaller networks but on larger ones, with Gigabit Ethernet, snort can become unreliable. Snort doesn't require that you recompile your kernel or add any software or hardware to your existing distribution but it does require that you have root privileges.